Innovative earthing systems for electric power substations using conductive nanoparticles - Ahmed Thabet; Youssef Mobarak (Institute of Advanced Engineering and Science, 2021)
The earthing system is very important to safe human’s lives and protect power system from normal and abnormal faults. High soil resistivity regions is the main problem of installation the earthing systems in electric power substations to pass the current through the earth's surface. This paper has been overcome on high soil resistivity regions by penetrating conductive nanoparticles to have extremely low grounding resistance. Moreover, it has been succeeded to examine the methodology of the proposed Nano-Tech earthing systems in case of single rods, multiple rods and grids. Also, it has been defined optimal types and concentrations of nanoparticles for Nano-Tech grounding system to provide excellence protection for electrical substations with respect to built beneath of soil where substation is located. A comparative study has been discussed and analyzed the results of traditional and nanotechnology grounding systems.